Targeting microglial TLR3–NF-κB/MAPK and JAK/STAT Axis: PEITC as a suppressor of poly (I:C)-induced neuroinflammation - Yi-Ching Lan; Yan-Ru Xiao; Yow-Wen Hsieh; Yih-Dih Cheng; Shu-Fen Peng; Fu-Shin Chueh; Hsu-Tung Lee; Yu-Sheng Hsieh; Wei-Cheng Jiang; Wen-Tsong Hsieh; Yu-Cheng Chou (Toxicology and Applied Pharmacology, 2026)

Finite strain pattern inferred from magnetic fabrics across the southern portion of the Central Range, Taiwan - Ya-Chu Tseng; En-Chao Yeh; Ning-Shan Hui; Yu-Min Chou; Jian-Cheng Lee; Ching-Chou Fu (Tectonophysics, 2026)

Anomalous fluid emissions at the Chung-lun mud pool, southwestern Taiwan: evidence for seismic–pore fluid interactions in a thrust fault system - Ching-Chou Fu; Jens Heinicke; Tsanyao Frank Yang; Vivek Walia (International Journal of Earth Sciences, 2026)

Geochemical signatures of mud and core gases from the Milun Fault Scientific Drilling (MiDAS), Taiwan: Implications for fluid pathways and crustal degassing - Ching-Chou Fu; Kuo-Hang Chen; Kuo-Wei Wu; Pei-Ling Wang; Ai-Ti Chen; Vivek Walia; Kuo-Fong Ma (Chemical Geology, 2026)

Corrigendum to “Investigation of seasonal variations in submarine groundwater discharge using radium isotopes under drought conditions in northwestern coastal Taiwan” [J. Hydrol. 649 (2025) 132450] - Minh-Quan Dang; Feng-Hsin Hsu; Chih-Chieh Su; Shih-Jung Wang; Ching-Chou Fu; In-Tian Lin (Journal of Hydrology, 2025)

Investigation of seasonal variations in submarine groundwater discharge using radium isotopes under drought conditions in northwestern coastal Taiwan - Minh-Quan Dang; Feng-Hsin Hsu; Chih-Chieh Su; Shih-Jung Wang; Ching-Chou Fu; In-Tian Lin (Journal of Hydrology, 2025)

Multicenter study on clinical outcomes and poor prognostic factors in patients with Klebsiella pneumoniae bacteremia receiving cefoperazone/sulbactam treatment - Tsung-Ta Chiang; Ming-Hsien Chiang; Hung-Jen Tang; Zhi-Yuan Shi; Mao-Wang Ho; Chia-Hui Chou; Shang-Yi Lin; Po-Liang Lu; Ting-Shu Wu; Shian-Sen Shie; Jien-Wei Liu; Feng-Yee Chang; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2024)
Background Infections caused by Klebsiella pneumoniae are common and result in high mortality rates. In vitro studies demonstrated the potency of cefoperazone/sulbactam (CPZ/SUL) against Klebsiella pneumoniae . However, the clinical efficacy of CPZ/SUL for the treatment of K. pneumoniae bacteremia has not been studied. Objectives This study aimed to associate the clinical outcomes of patients with bacteremia with the minimal inhibitory concentrations (MICs) of CPZ/SUL against the causative K. pneumoniae isolates. Methods This multicenter, retrospective study was conducted in Taiwan between July 2017 and April 2021. Patients with K. pneumoniae bacteremia treated with CPZ/SUL were enrolled in this study. CPZ/SUL MICs were determined using the agar dilution method. Data on the patients’ clinical outcomes and characteristics were collected and analyzed. Results In total, 201 patients were enrolled. Among the causative K. pneumoniae isolates, 180 (89.5%) were susceptible to CPZ/SUL. Most patients ( n = 156, 77.6%) had favorable outcomes. The 30-day mortality rate was 11.9% ( n = 24). Multivariate risk analyses showed that higher APACHE II score (Odds Ratio [OR], 1.14; Confidence Interval [CI], 1.07–1.21; p < 0.001), metastatic tumors (OR, 5.76; CI, 2.31–14.40; p < 0.001), and causative K. pneumoniae CPZ/SUL MICs > 16 µg/ml (OR, 4.30; CI, 1.50–12.27; p = 0.006) were independently associated with unfavorable outcomes. Conclusion Patients with K. pneumoniae bacteremia treated with CPZ/SUL at a ratio 1:1 had favorable outcomes when the CPZ/SUL MICs were ≤ 16 µg/ml. Patients with higher APACHE II scores and metastatic tumors had unfavorable outcomes.

Real-time database for geochemical earthquake precursory research - Arvind Kumar; Vivek Walia; Shih-Jung Lin; Ching-Chou Fu (Natural Hazards, 2020)

Soil gas survey in and around Shanchiao fault of northern Taiwan for establishing continuous monitoring station - Arvind Kumar; Vivek Walia; Yi-Chun Sung; Shih-Jung Lin; Ching-Chou Fu; Kuo-Liang Wen (Acta Geophysica, 2018)

Effects of normoxic and hypoxic exercise training on the bactericidal capacity and subsequent apoptosis of neutrophils in sedentary men - Yi-Ching Chen; Wan-Yu Chou; Tieh-Cheng Fu; Jong-Shyan Wang (European Journal of Applied Physiology, 2018)

MicroRNA let-7g cooperates with interferon/ribavirin to repress hepatitis C virus replication - Wen-Wen Chou; Chung-Feng Huang; Ming-Lun Yeh; Yi-Shan Tsai; Ming-Yen Hsieh; Ching-I Huang; Jee-Fu Huang; Pei-Chien Tsai; Edward Hsi; Suh-Hang Hank Juo; Wei-Lun Tsai; Wan-Long Chuang; et al. (Journal of Molecular Medicine, 2016)

Identifications and removal of diurnal and semidiurnal variations in radon time series data of Hsinhua monitoring station in SW Taiwan using singular spectrum analysis - Arvind Kumar; Vivek Walia; Baldev Raj Arora; Tsanyao Frank Yang; Shih-Jung Lin; Ching-Chou Fu; Cheng-Hong Chen; Kuo-Liang Wen (Natural Hazards, 2015)

Cloning of Two New cry Genes from Bacillus thuringiensis subsp. wuhanensis Strain - White-Shang Kuo; Jong-Huon Lin; Ching-Chou Tzeng; Shui-Shang Kao; Kin-Fu Chak (Current Microbiology, 2000)